2015
DOI: 10.1016/j.stem.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNA-Seq of Human Motor Neurons Implicates Selective ER Stress Activation in Spinal Muscular Atrophy

Abstract: SUMMARY Spinal Muscular Atrophy (SMA) is caused by mutations in the SMN1 gene. Because this gene is ubiquitously expressed, it remains poorly understood why motor neurons (MNs) are one of the most affected cell types. To address this question, we carried out RNA-sequencing studies using fixed, antibody-labeled and purified MNs produced from control and SMA patient-derived induced pluripotent stem cells (iPSCs). We found SMA-specific changes in MNs, including hyper-activation of the endoplasmic reticulum (ER) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 35 publications
(47 reference statements)
7
104
4
3
Order By: Relevance
“…Our findings reveal that SMN deficiency induces selective MN death in vitro that is mediated by cell autonomous mechanisms. This is in agreement with previous in vitro and in vivo studies that used stem cell-derived mouse and human MNs (Ebert et al, 2009; Makhortova et al, 2011; Sareen et al, 2012; Ng et al, 2015) as well as selective restoration of SMN in MNs of SMA mice (Gogliotti et al, 2012; Martinez et al, 2012; McGovern et al, 2015) and conditional SMN depletion from MNs of wild type mice (Park et al, 2010; McGovern et al, 2015). Thus, our model system recapitulates a key feature of the human disease and supports the conclusion that SMN reduction has differential effects on the survival of MNs relative to other types of neurons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings reveal that SMN deficiency induces selective MN death in vitro that is mediated by cell autonomous mechanisms. This is in agreement with previous in vitro and in vivo studies that used stem cell-derived mouse and human MNs (Ebert et al, 2009; Makhortova et al, 2011; Sareen et al, 2012; Ng et al, 2015) as well as selective restoration of SMN in MNs of SMA mice (Gogliotti et al, 2012; Martinez et al, 2012; McGovern et al, 2015) and conditional SMN depletion from MNs of wild type mice (Park et al, 2010; McGovern et al, 2015). Thus, our model system recapitulates a key feature of the human disease and supports the conclusion that SMN reduction has differential effects on the survival of MNs relative to other types of neurons.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our model system recapitulates a key feature of the human disease and supports the conclusion that SMN reduction has differential effects on the survival of MNs relative to other types of neurons. While the precise molecular mechanisms remain to be fully elucidated, recent work has implicated selective activation of ER stress in the death pathway of SMA MNs (Ng et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Previously, low levels of SMN have been linked to widespread changes in expression patterns, [121][122][123][124][125][126][127][128] but it is currently an open question as to how these changes might be linked to Cajal bodies. In addition, the mechanism by which these conformational changes in the nucleus affect the rest of the cell and which cellular components and processes are most severely affected has yet to be studied.…”
Section: Smn and Cajal Body Structurementioning
confidence: 99%
“…We previously showed that, consistent with the clinical features of the disease in SMA patients, spinal motor neurons innervating proximal muscles are preferentially affected and degenerate early in the disease process compared to those that innervate distal muscles and are relatively spared (Mentis et al, 2011). To date, several effector pathways have been implicated in the process of motor neuron death in SMA, which include tau phosphorylation (Miller et al, 2015), ER stress (Ng et al, 2015), and c-Jun N-terminal kinase 3 (JNK3) activation (Genabai et al, 2015) among others. However, the events that trigger degeneration of motor neurons, but not of other spinal neurons in SMA remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%